Associations of park features with park use and park-based physical activity in an urban environment in Asia: A cross-sectional study. (May 2022) - Petrunoff, Nicholas A.; Edney, Sarah; Yi, Ng Xian; Dickens, Borame L.; Joel, Koo Ruihan; Xin, Wang Nan; Sia, Angelia; Leong, Duncan; van Dam, Rob M.; Cook, Alex R.; Sallis, James F.; Chandrabose, Manoj; et al.
Abstract: Park use is associated with health, yet our understanding of park features related to their use is limited. Singapore's parks were audited for 30 micro-features, then geospatial analysis characterized micro-features scores for parks nearest to participants' homes. Adults (3, 435) reported their park use and park-based physical activity. Using linear regression models, we found living near a park with higher micro-features scores was associated with more time in parks and park-based physical activity. Specific micro-features were associated with more park time (wildlife areas, water features, forested areas, unpaved trails (2–2.6 h/month, p < 0.05)) and with physical activity in parks (water features, forested areas, large playground, open green spaces (1.8–2.2 h/month, p < 0.05)). These findings could inform parks planning to support population-health. Highlights: Park use is associated with health. Despite being amenable to change, research on micro-level park features is scant. We audited all public parks in Singapore for 30 micro-features. Specific features were associated with more park time (e.g. unpaved trails) and with park-based physical (e.g. forested areas). These findings may inform the planning of parks that promote health.